Economic analysis of healthcare-associated infection prevention and control interventions in medical and surgical units: systematic review using a discounting approach. Issue 1 (September 2020) - Tchouaket Nguemeleu, E.; Beogo, I.; Sia, D.; Kilpatrick, K.; Séguin, C.; Baillot, A.; Jabbour, M.; Parisien, N.; Robins, S.; Boivin, S.
SUMMARY: Nosocomial or healthcare-associated infections (HCAIs) are associated with a financial burden that affects both patients and healthcare institutions worldwide. The clinical best care practices (CBPs) of hand hygiene, hygiene and sanitation, screening, and basic and additional precautions aim to reduce this burden. The COVID-19 pandemic has confirmed these four CBPs are critically important prevention practices that limit the spread of HCAIs. This paper conducted a systematic review of economic evaluations related to these four CBPs using a discounting approach. We searched for articles published between 2000 and 2019. We included economic evaluations of infection prevention and control of Clostridioides difficile- associated diarrhoea, meticillin-resistant Staphylococcus aureus, vancomycin-resistant enterococci, and carbapenem-resistant Gram-negative bacilli. Results were analysed with cost-minimization, cost-effectiveness, cost-utility, cost-benefit and cost-consequence analyses. Articles were assessed for quality. A total of 11, 898 articles were screened and seven were included. Most studies (4/7) were of overall moderate quality. All studies demonstrated cost effectiveness of CBPs. The average yearly net cost savings from the CBPs ranged from $252, 847 (2019 Canadian dollars) to $1, 691, 823, depending on the rate of discount (3% and 8%). The average incremental benefit cost ratio of CBPs varied from 2.48 to 7.66. In order to make efficient use of resources and maximize health benefits, ongoing research in the economic evaluation of infection control should be carried out to support evidence-based healthcare policy decisions.